Propuesta de mitigación para la congestión vehicular a través de corredores de vida alternativos para la ciudad de Armenia, Quíndio, Colombia. (2021)
Throughout history, the city of Armenia has been confronted with a major urban problem that triggers other kinds of problematic situations in the city, mobility, because as we know, In Colombia the cities were not planned with an expansion of transport, this being one of the basic needs of the human being, because as the development of the city took place the automotive sector was very still. It was not until after a few years that it began to grow abruptly by looking for space where there wasn’t even one. Thanks to this, the cities face this problem that is currently being confronted with urban interventions, zoning plans, alternative transport, among others. Armenia concentrates this problem in the center of the city, the increase of vehicles and tourists makes the access too congested and besides this the quality of life in this precious city is reduced. There are 2 major avenues that cross the city from the center to the north, which are Centenario and Bolivar Avenues but are not used to the maximum for the decongestion of the city; So, the Corredores de Vida project seeks to make this possible through the intervention of these two great avenues, making them urban corridors friendly to the environment and prioritizing pedestrians, besides the inclusion of the tram becoming the second city of Colombia to possess this type of transport, and the pedestrianization of the center of the city giving solution to that great problem that has left us with the bad planning of the city since its beginnings.